Leveraging the service innovation of local medical universities in China: the perspective of teachers’ professional development / Lu Liu ... [et al.] - Lu, Liu; Boo, Ho Voon; Hamzah, Muhammad Iskandar; Jia, Jie He (Universiti Teknologi MARA Cawangan Kedah, 2023)
The sudden COVID-19 outbreak in 2020 has affected global human health and brought new opportunities and challenges to people's life and social development. In such a social environment, the Chinese government has proposed to accelerate the reform of medical education. However, as the main body of education, Teachers’ Professional Development (TPD) has lagged behind in recent years. This study uses ERG as the theoretical basis, establishes the theory and proposed research hypotheses. The conclusion is that universities should establish the cultural concept of "service support" based on TPD. Change from teaching service-to-service support for teachers' comprehensive development, from single organization service support to whole process and whole-staff service support. According to the characteristics of teachers, professional standards and social requirements for teachers transformed into self-development needs of teachers themselves as human beings, to stimulate the initiative and creativity of teachers' work and realize their self-growth.